The Set of Alfonsine Tables Underlying Giovanni Bianchini’s Planetary Tables - Chabás, José; Goldstein, Bernard R. (Aestimatio, 2022)
The analysis of astronomical tables has proven to be a powerful tool to understand the transmission of astronomical knowledge. Further, the study of the major sets of tables compiled or in circulation in the Middle Ages has contributed significantly to mapping the thousands of tables preserved in medieval manuscripts. The present paper focuses on the relationship between two specific sets of tables, both in the framework of Alfonsine astronomy: one of hitherto uncertain authorship and a much larger one compiled by the Ferrarese astronomer Giovanni Bianchini (d. after 1469).